Farmers Inaccessibility to Agricultural Credit in Nyandarua District, Kenya - Vincent, Ng’eno; Muiruri, Erick Jotham; Nyangweso, Philiph Mulama; Langat, B. K.; Kipsat, Mary Jepkemboi (Asian Journal of Agriculture and Rural Development, 2011)
Smallholder farmers face various challenges in production one of them being inaccessibility to credit. This study specifically sought to identify household socio-economic characteristics and institutional requirements influencing access to credit among smallholder farmers in Nyandarua District. The study used a Logit model. Both quantitative and qualitative data were acquired from primary and secondary sources. Primary data was collected using questionnaires through a survey design. A sample of 264 smallholder farmers was selected using stratified, multi-stage random sampling techniques. Data was analyzed using descriptive statistics and regression analysis using Statistical Package for Social Sciences (SPSS). The study established that socio-economic constraints such as age, gender, household size, farm income, collateral and awareness are critical determinants of access to credit. The study concludes that household socio-economic characteristics do influence access to credit. Key recommendations made include the need by government to deal with bureaucracies involved in land registration to benefit majority of smallholder farmers who remain insecure in the land they use without proof of ownership and also to make easier the registration of lease certificates for those who do not own land and use land on leasehold tenure system. Financial institutions should also put in place less stringent credit requirements and reduce credit costs especially interest rates to make credit more affordable.